Acoustofluidic cell micro-dispenser for single cell trajectory control. Issue 18 (18th August 2022) - Richard, Cynthia; Devendran, Citsabehsan; Ashtiani, Dariush; Cadarso, Victor J.; Neild, Adrian
Abstract : A surface acoustic wave micro-dispenser for the on-demand trap and release of single cells with trajectory control. Abstract : The precise manipulation of individual cells is a key capability for the study of single cell physiological characteristics or responses to stimuli. Currently, only large cell populations can be transferred with certainty using expensive and laborious flow cytometry platforms. However, when approaching small populations of cells, this task becomes increasingly challenging. Here, we report an effective acoustofluidic micro-dispenser, utilising surface acoustic waves (SAWs), with the ability to trap and release cells on demand, which when combined with an external valve can guide the trajectory of individual cells. We demonstrate single cell trap and release with a single cell trapping effectiveness of 74%, enabling the capability of dispensing a highly controlled amount of cells without any harmful effects. This device has the potential to be easily integrated into a wide range of analytical platforms for applications such as single cell fluorescent imaging and single cell proteomic studies.